Implementasi Algoritma Greedy dan Djikstra untuk Efektifitas Rute Pariwisata Populer di Borobudur - Eka Rahmawati; Candra Agustina (Jurnal Teknologi Informasi dan Terapan, 2021)
New tourist attractions in the Borobudur region always bring domestic and foreign tourists to visit. Besides visit the Borobudur Temple, now, the tourists can visit the other popular tourist attractions near the main destination. For example, in 2019, a new tourist attraction was created, it called Mata Langit. Many tourists will include all the interest object on the visit list. The more destinations that will be visited will increase the allocation of time to travel. Tourists must be careful in determining the route. The effective route is very important to manage the time. In the field of computer technology, several algorithms can help to determine the shortest route. Among them are the Greedy algorithm and Djikstra's algorithm. Both algorithms have different principles in processing data. Therefore to get the best results, it is necessary to compare the 2 algorithms. The first time, determined the 5 most popular attractions in Borobudur based on the number of visitors in the last three months. Then the data is processed using Greedy and Djikstra's algorithm. The winner is determined based on the shortest time owned by each route produced. The results obtained show that the Greedy algorithm is more effective in calculating the shortest route to visit popular tours in Borobudur